Structural Distortions and Decentralized Fiscal Policies in EMU - Roel Beetsma; Lans Bovenberg (Center for Economic Studies and ifo Institute (CESifo), 2001)
The combination of discretionary monetary policy, labor-market distortions and nominal wage rigidity yields an inflation bias as monetary policy tries to exploit nominal wage contracts to address labour-market distortions Although an inflation target eliminates this inflation bias, it creates a conflict between monetary policy and discretionary fiscal policy if fiscal policy is set at a higher frequency than nominal wages are. To avoid the associated excessive accumulation of public debt, ceilings on public debt are called for. If countries differ substantially in terms of structural distortions or economic shocks, uniform debt ceilings must be complemented by country-specific debt targets in order to prevent decentralised fiscal authorities from employing debt policy strategically.
Keywords: E52; E58; E61; E62; 330; Discretionary monetary policy; wage rigidity; decentralized fiscal policy; monetary union; inflation targets; debt targets